2022
DOI: 10.3390/buildings12040449
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of BIM Energy Analysis and Monte Carlo Simulation for Estimating Building Energy Performance Based on Regression Approach: A Case Study

Abstract: The energy performance prediction of buildings plays a significant role in the design phases. Theoretical analysis and statistical analysis are typically carried out to predict energy consumption. However, due to the complexity of the building characteristics, precise energy performance can hardly be predicted in the early design stage. This study considers both building information modeling (BIM) and statistical approaches, including several regression models for the prediction purpose. This paper also highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Since experimental work in the existing buildings is limited primarily due to economic constraints, simulation software was used to evaluate and improve energy use in residential buildings in a mild-dry climate zone. A similar method was used in [29][30][31][32][33][34][35][36]46,47]. However, this work is based on six main aspects, which were derived from various building energy standards: envelope components, building area features, HVAC systems, service water heating systems, lighting systems, and plug loads.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since experimental work in the existing buildings is limited primarily due to economic constraints, simulation software was used to evaluate and improve energy use in residential buildings in a mild-dry climate zone. A similar method was used in [29][30][31][32][33][34][35][36]46,47]. However, this work is based on six main aspects, which were derived from various building energy standards: envelope components, building area features, HVAC systems, service water heating systems, lighting systems, and plug loads.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the study did not cover the potential of improving the developed models in a practical and standardized way. Some other papers, such as [32,36], used ASHRAE thermal comfort standards and practical energy-saving strategies to optimize thermal comfort in residential buildings of Cairo (Egypt) and energy performance in China's existing residential buildings. The findings showed that in terms of increasing energy efficiency and thermal comfort, energy-efficient rehabilitation was worth carrying out to enhance existing residential buildings.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To be more specific, Building Energy Performance Simulation (BEPS) tools based on BIM, for example, Autodesk software, was used to build prototypes and simulate energy usage. Additionally, computer mathematical techniques such as the Monte Carlo simulation were utilized to assist in simulating energy usage for various building layouts [4]. Additionally, a variety of statistical tools, including the programming language R, were employed to build a set of linear regression equations for parametric and sensitivity analyses.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…erefore, any change in consumer behavior is based on recognizing their consumption behavior and on promoting energy management recommendations in the field of energy [4]. It is necessary to subscribe to the consumption pattern of subscribers, including their status, knowledge, attitude, and consumption behavior that should be studied, and with the understanding of the objective conditions of consumers, appropriate strategies and programs should be formulated and presented [5,6].…”
Section: Introductionmentioning
confidence: 99%